2017
DOI: 10.1590/0102-6720201700020012
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Enemas Containing Sucralfate in Tissue Content of Muc-2 Protein in Experimental Model of Diversion Colitis

Abstract: Background: The effects of topical application of sucralfate (SCF) on the tissue content of MUC-2 protein have not yet been evaluated in experimental models of diversion colitis. Aim: To measure the tissue content of MUC-2 protein in the colonic mucosa diverted from fecal stream submitted to the SCF intervention. Methods: Thirty-six rats underwent derivation of intestinal transit through proximal colostomy and distal mucous fistula. The animals were divided into three groups which were submitted application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 33 publications
(52 reference statements)
0
16
0
7
Order By: Relevance
“…Recently, other authors have evaluated the effects of enemas with SCF to treat the experimental DC 14,[27][28][29] . These studies showed that SCF reduces the inflammatory process, decreases neutrophil infiltration and oxidative tissue damage in colonic segments devoid of exposure to the fecal stream 29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, other authors have evaluated the effects of enemas with SCF to treat the experimental DC 14,[27][28][29] . These studies showed that SCF reduces the inflammatory process, decreases neutrophil infiltration and oxidative tissue damage in colonic segments devoid of exposure to the fecal stream 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the capacity of SCF to stimulate the production of mucins and EGF, it was demonstrated that the use of SCF enemas stimulates the Table 1 -Tissue content of E-cadherin, β-catenin and MDA in colonic mucosa devoid of fecal stream submitted to intervention with daily enemas with saline or SCF at concentration of 1 or 2 g/kg for two or four weeks. production of different subtypes of colonic mucins by cells of the colonic epithelium, favoring mucosal healing 14,[27][28][29] . These results confirm the effectiveness of SCF in stimulating the production of the mucins and in reducing the oxidative damage and the inflammation of the intestinal mucosa 14,[26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When temporary, an average of three months is estimated for intestinal reconstruction, however, this timeframe may be extend into years due to multiple factors. 1 The colostomy using Hartmann's procedure, which involves sigmoid colon exteriorization and rectum exclusion from intestinal transit, accounts for half of the total intestinal transit deviations performed, which also makes this type of stoma the one with the highest number of complications, especially in the long run. Thus, in cases where intestinal transit diversion remains for more than 6 months, the number of complications increases, including Disuse Colitis (DC).…”
Section: Introductionmentioning
confidence: 99%